Interpreta y representa números naturales hasta cuatro cifras - Huamán Huamán, Margarita (2018)
The present elaboration of the design of the learning session is constituted by functional strategies that lead to develop the cognitive processes towards the students, having as support the pedagogical (recurrent) and didactic processes, which guide the achievement of meaningful learning, in the which also develops the reasoning, the creativity of the students It is likewise that in this learning session that corresponds to the area of. Mathematics responds to the needs of students to know the Position value in numbers of up to four digits using structured material as base 10. This session is comprised for its three moments and the problem solving approach, which will allow us to be clear about what we want the students to be intrinsically appropriated in their formation.